2015
DOI: 10.4103/0019-509x.178380
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P450 1A1 genetic polymorphisms as cancer biomarkers

Abstract: Phase I metabolic enzyme CYP1A1 plays an important role in xenobiotics metabolism and has been extensively studied as a cancer risk biomarker. CYP1A1 is polymorphic and its four variants, e.g., CYP1A1* 2 A, CYP1A1* 2C, CYP1A1* 3 and CYP1A1* 4 with trivial names m1, m2, m3, and m4 respectively, are most commonly studied for cancer link. Gene- gene interaction studies combining polymorphisms of this enzyme with those of phase II detoxifying enzymes, especially glutathione S- transferases (GSTs) revealed greater … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 1 publication
0
8
1
Order By: Relevance
“…In addition, the results published by Li et al [22] revealed that no correlation between T3801C polymorphism of CYP1A1and predisposition to PCa. Nevertheless, many studies diverge from our results: Bag et al [10], Vijayalakshmi et al [23], Shaik et al [24] and He et al [25] postulated a strong involvement of CYP1A1 polymorphism T3801C in PCa development.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…In addition, the results published by Li et al [22] revealed that no correlation between T3801C polymorphism of CYP1A1and predisposition to PCa. Nevertheless, many studies diverge from our results: Bag et al [10], Vijayalakshmi et al [23], Shaik et al [24] and He et al [25] postulated a strong involvement of CYP1A1 polymorphism T3801C in PCa development.…”
Section: Discussioncontrasting
confidence: 96%
“…Eleven polymorphisms of CYP1A1 have been described, four of which have been the most studied for their involvement in modifying the risk of carcinogenesis: m1 (T3801C), m2 (A2455G), m3 (T3205C) and m4 (C2453A) [9]. The CYP1A1 3801T/C (also named MspI polymorphism, *2A or m1), results from a replacement of thymine by a cytosine at the 3801st base pair in the 3' flanking region of the gene [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the wild-type (CYP1A1*1 ), 10 variant alleles have been identified [7]. Variants CYP1A1*2A, CYP1A1*2C, CYP1A1*3 and CYP1A1*4 with trivial names m1, m2, m3 and m4 ; respectively were the most commonly studied for cancer link [20, 21]. …”
Section: Discussionmentioning
confidence: 99%
“…It is known that cisplatin selectively accumulates in the proximal tubule, leading to oxidative stress, inflammation, and vascular injury, and subsequent renal pathology [ 10 ]. The degree to which cisplatin and its metabolites accumulate and induce injury can be influenced by the coordinated activity of uptake and efflux transport proteins on the basolateral and apical membranes of the kidney proximal tubules [ 11 ]. Cisplatin metabolism is also important in governing proximal tubule exposure to the parent drug and its conjugates [ 12 ].…”
Section: Introductionmentioning
confidence: 99%